Analisis Survei Kepuasan Masyarakat Pada Badan Riset Dan Inovasi Daerah Kota Medan - Yafi Bayu Ahmad Siregar; Yogi Saputra; Naufal Yudhi Handika; Dimas Lufti; Muhammad Donni Lesmana Siahaan (CV. Hawari, 2024)
Public services are very important, both in tangible form for the community and services for the community. The higher the quality of public services, the various conveniences you will get, meaning there will be no problems that hinder you from carrying out all your needs. Meanwhile, services in the form of services are really needed by the community, such as services for making letters of recommendation. The quality of service at the Medan City Regional Research and Innovation Agency Office is in category